2020
DOI: 10.1364/josab.396471
|View full text |Cite
|
Sign up to set email alerts
|

Optimized design for a terahertz parametric oscillator based on degenerate four-wave mixing in silicon nitride

Abstract: We propose terahertz wave generation using a parametric oscillator based on phase-matched and non-phase-matched degenerate four-wave mixing processes within a silicon nitride Fabry–Perot microcavity. The central frequency of the generated terahertz waves would be tunable over the frequency range of 3.6–5.73 THz by varying the wavelength of the pump wave. The best phase-matching condition is achieved at a frequency of 5 THz, and an optimum peak power of 329 W is obtained at a frequency of 4.29 THz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[11][12][13][14] Furthermore, the generation of THz picosecond pulses has rarely been considered in previous studies. 15,16 This manuscript proposed a Si-based WTPO system and numerically investigated the operating characteristics of a picosecond synchronously pumped scheme. The frequency range of the output THz-wave for the silicon membrane waveguide is determined by calculating the phase-matching conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Furthermore, the generation of THz picosecond pulses has rarely been considered in previous studies. 15,16 This manuscript proposed a Si-based WTPO system and numerically investigated the operating characteristics of a picosecond synchronously pumped scheme. The frequency range of the output THz-wave for the silicon membrane waveguide is determined by calculating the phase-matching conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical and experimental studies on the FWM effect in silicon‐based waveguides have shown that this method is feasible to realize a compact and efficient THz source 11–14 . Furthermore, the generation of THz picosecond pulses has rarely been considered in previous studies 15,16 …”
Section: Introductionmentioning
confidence: 99%